Knowledge and attitudes of adolescents about HPV and HPV vaccines - Ristić, Dajana (PONS - medicinski časopis, 2022)
INTRODUCTION: HPV is a major health problem. It is the cause of cervical cancer and the most common sexually transmitted disease. There are several types of HPV (high risk - 16, 18). Primary prevention of infection, education of young people and vaccination are very important in the prevention of cervical cancer. AIM: Determining the level of knowledge and attitudes towards HPV and HPV vaccine, and the importance of education adapted to the age of the respondents. METHODS: The research was conducted in the population of high school students, aged 15 to 19. The sample consisted of 260 respondents. Adult respondents voluntarily gave their written consent to participate in the research, and minors participated with the consent of their parents. SPSS was used for statistical data processing, and descriptive statistics and the x2 test were used for statistical analysis. RESULTS: Out of the total number of respondents, only 3% of students gave completely correct answers to the questions directed towards HPV and the HPV vaccine. Almost half of the respondents (49%) do not want to be vaccinated, and 80% do not know if there is a vaccine in Bosnia and Herzegovina. CONCLUSION: The knowledge shown by the students is unsatisfactory.